2015
DOI: 10.1063/1.4919115
|View full text |Cite
|
Sign up to set email alerts
|

Strong mode-mode interactions in internal solitary-like waves

Abstract: Classical linear theory presents vertically trapped internal waves of different modes as completely uncoupled. This description carries over to the simplest weakly nonlinear theory for internal solitary waves, the Korteweg-de Vries theory. The balance between weakly nonlinear and dispersive effects in this theory allows for soliton solutions, meaning that waves emerge from collisions without changing form. However, exact mode-1 internal solitary waves have been shown to exhibit departures from soliton behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 30 publications
4
21
0
Order By: Relevance
“…Similar to the case 1, the characteristics and energy loss of the amplitude-modulated wave packet for the case 5 were also similar with the breather definition. Noted that the breather solution exist only if the cubic nonlinearity coefficients in Gardner equation is positive (Lamb et al, 2007), but the configuration of the stratification in our simulation results a negative cubic nonlinearity coefficient in Gardner equation (Grimshaw et al, 2010;Talipova et al, 2011) and it means the breather is not allowed The oscillating tail was frequently observed in similar studies (Carr et al, 2015;Olsthoorn et al, 2013;Stastna et al, 2015). Its generation was related to the shear, and the tail was sustained by continuous energy input.…”
mentioning
confidence: 60%
“…Similar to the case 1, the characteristics and energy loss of the amplitude-modulated wave packet for the case 5 were also similar with the breather definition. Noted that the breather solution exist only if the cubic nonlinearity coefficients in Gardner equation is positive (Lamb et al, 2007), but the configuration of the stratification in our simulation results a negative cubic nonlinearity coefficient in Gardner equation (Grimshaw et al, 2010;Talipova et al, 2011) and it means the breather is not allowed The oscillating tail was frequently observed in similar studies (Carr et al, 2015;Olsthoorn et al, 2013;Stastna et al, 2015). Its generation was related to the shear, and the tail was sustained by continuous energy input.…”
mentioning
confidence: 60%
“…The effect of the Earth's rotation is neglected, and hence the simulations are performed in an inertial frame of reference. A complete description of the numerical model used in this study can be found in Subich et al (2013), where a detailed validation and accuracy analysis through several test cases is also given. The model employs a spectral collocation method, which yields highly accurate results at moderate grid resolutions.…”
Section: Governing Equations and Numerical Methodsmentioning
confidence: 99%
“…The interaction between internal waves of different length scales also occurs naturally (Sun and Pinkel, 2012). When the disparity in length scales between the participating waves is large, the relatively smaller length scale wave essentially plays the role of the disturbance to the "background flow" 2 C. Xu and M. Stastna: ISW-short wave interaction induced by the relatively larger length scale wave, as they interact with each other.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations